The Bellevue Wreck: A Recent Survey of a Large Late Medieval Shipwreck in Dalarö Harbour, Sweden: A Possible Hulk?. (2nd January 2021) - Eriksson, Niklas
ABSTRACT: It has been known that a large, clinker-built shipwreck lies on the seabed near the Hotel Bellevue in Dalarö in the Stockholm archipelago since the 1960s. The wreck has been the subject of several small-scale archaeological investigations. This article reports the results of recent marine archaeological fieldwork that concluded that the Bellevue wreck is the remains of a late medieval ship equipped with a forecastle. Moreover, the analysis shows that it was a larger vessel for its day. The article argues that the wreck resembles what may be referred to as a hulk.